Larvae of the sand stargazer Sindoscopus australis and notes on the development of Dactyloscopidae (Perciformes: Blennioidei) - Herrera, Guillermo A.; Llanos-Rivera, Alejandra; Landaeta, Mauricio F. (Zootaxa, 2007)
Pre- and post-flexion larvae of the temperate sand stargazer Sindoscopus australis (Dactyloscopidae, Blennioidei) in the size range of 4.4 to 16.0 mm are described using specimens collected in nearshore plankton samples inside bays of Central Chile. The larvae are elongate with a pointed snout, a large head and a short and compact gut with short preanal distance. They show pigmentation at the cleithral symphysis, above the gut, ventrally at the otic capsules, and on the ventrum. They lack pigment dorsally on the head. Although the larvae of three dactyloscopid genera remain undocumented, the available evidence suggests that some larval characters are indicative of phylogenetic affinities. The phylogenetically primitive genus Platygillellus has paired melanophores on the head, a generalized feature common to basal blennioids (e.g. Blenniidae and Tripterygiidae). The derived genera show two conditions: the larvae of the related genera Gillellus and Sindoscopus lack dorsal cephalic pigmentation; the larvae of the species of the clade Myxodagnus - Dactylagnus plus Dactyloscopus have a single large melanophore dorsally on the head and ventrally on the gut.